The functional polymorphisms of VDR, GC and CYP2R1 are involved in the pathogenesis of autoimmune thyroid diseases. (1st October 2014) - Inoue, N; Watanabe, M; Ishido, N; Katsumata, Y; Kagawa, T; Hidaka, Y; Iwatani, Y
Summary: Vitamin D is a multi-functional immune regulator, and a low serum concentration of vitamin D promotes autoimmune inflammation. In this study, we evaluate the association between the prognosis of autoimmune thyroid disease (AITD) and the functional polymorphisms of genes that regulate vitamin D metabolism. For 139 Graves' disease (GD) patients, 116 Hashimoto's disease (HD) patients and 76 control subjects, we genotyped the following polymorphisms using polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP): vitamin D receptor (VDR): rs731236, rs7975232, rs2228570 and rs1544410; group-specific component (GC): rs7041 and rs4588; and CYP2R1: rs10741657. The frequency of the TT genotype for the rs731236 polymorphism was higher in GD patients than in HD patients ( P = 0·0147). The frequency of the C allele for the rs7975232 polymorphism was higher in GD patients than in control subjects ( P = 0·0349). The proportion of GD patients whose anti-thyrotrophin receptor antibody (TRAb) level was >51% was higher in those with the CC genotype than in those with the CA+AA genotypes ( P = 0·0065). The frequency of the CC genotype for the rs2228570 polymorphism was higher in HD patients than in control subjects ( P = 0·0174) and GD patients ( P = 0·0149). The frequency of the Gc1Gc1 genotype for the GC polymorphism and the AG genotype for the CYP2R1 polymorphism were lower in intractable GD than in GD in remission ( P = 0·0093 and 0·0268, respectively). In conclusion, genetic differences in the VDR gene may be involved in the development of AITD and the activity of GD, whereas the genetic differences in the GC and CYP2R1 genes may be involved with the intractability of GD.